Effects of NR/SBR ratio on mechanical properties and artificial mechanical performance of anti-vibration bushings - Akyüz, Seher; Darı M.E.; Esiyok Y.E.; Ermeydan M.A. (Springer Science and Business Media Deutschland GmbH, 2021)
Rubber materials are utilized in automotive industry as anti-vibration bushes, engine mounts, and shock absorbers especially for the vibration, noise and shock absorbing purposes. General purpose elastomers are blended with each other to combine their individual properties in one material. It is worth mentioning here that with increasing demand in performance requirement, the usage of blends is almost inevitable. In this study, four natural rubber (NR)/styrene butadiene rubber (SBR) blends were formulated with different rubber ratios to produce anti-vibration bushings and to examine the effect of NR/SBR ratio on the performance of bushings. Dispersion of the rubber was also examined to observe the filling distribution of rubber recipes. The prepared rubber formulations were characterized by the rheological and physico-mechanical tests. It was found that the dispersibility and tensile strength of the rubber mixture increased by increasing NR ratio. The rubber formulations were vulcanized at 190 °C and 540–600 s, determined after some rheological and physico-mechanical tests. After vulcanization, static and dynamic mechanical tests on anti-vibration bushings were carried out to examine the effect of elastomer ratio on durability properties of products. We found that increasing NR ratio up to 70% is enough for lowest hysteresis and longer life-time for the anti-vibration products. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Anti-vibration; Bushings; Hysteresis; Natural rubber; Styrene butadiene rubber; Vulcanization